USE OF MODERN TECHNOLOGIES IN TEACHING PEDAGOGICAL SCIENCE (Conferencea, 2022)
This article talks about the technologies that can be used in the process of teaching pedagogy, its application to the educational process, and the possibilities of using modern technologies to improve the quality of education.